Transnational Tourism Programs in Vietnam: Students' Perspectives and a Practitioner's Reflection / Anh Hai Le ...[et al.] - Anh, Hai Le; Klieve, Helen; McDonald, Christine V. (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2015)
This paper examines an instructor and university students' views of different types of transnational tourism programs in Vietnam. A mixed methods research design, incorporating an online survey with 49 students, and an in-depth interview with one instructor, was utilised. Findings indicated that students had high expectations in both programs, but exhibited different satisfaction levels in the two programs. Students were generally satisfied with the program employing a fully adopted western curriculum, yet disappointed by the partially westernised program in which each provider accounts for 50% of the content. Findings from this study provide useful insights for transnational education providers, and tourism practitioners for future collaborations regarding curriculum development.